KERJASAMA PEMERINTAH DENGAN SWASTA (STUDI KASUS PENGELOLAAN PARKIR DI KOTA PEKANBARU) - Yadi Pranata; Harapan Tua (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research is motivated by the phenomenon of maximal management of common-street parking in the city of Pekanbaru. Still unclear parking management system in the city of Pekanbaru that cause various effects such as land use do not have permission to be used as a parking lot, causing traffic jams.This study aimed to investigate the implementation of the management conducted by the Department of Transportation UPTD Parking manage parking in the city of Pekanbaru and to identify factors - factors that affect the management of parking in the city of Pekanbaru. From the results of this study found several factors that affect the success of the management of parking, including factors that management systems are used, the coordination between the parties to the participation and awareness. The most dominating factor to cope with parking in the city of Pekanbaru permaslahan this is a factor of parking management system itself because this is the system that directs the management of this park.The research was conducted in the city of Pekanbaru precisely in UPTD Parking Pekanbaru City Department of Transportation. Key informants in this research is the Head Of UPTD Pparking, managers, parking attendants to the public. The sampling technique is snowball sampling in data collection used the method of observation, interviews and documentation. After the data were analyzed by using qualitative descriptive analysis.After a study found that the management of parking in the city of Pekanbaru has not been maximized, it can be seen from the theory of George R. Terry on the Management functions are reviewed based on four indicators, namely: planning, organizing, directing and monitoring.Keywords: Management System, Cooperation, Parking